Threatened / 2. - Schrefer, Eliot, 1978- (Ape Quartet, 2014)
Luc is an orphan, living in debt slavery in Gabon, until he meets a Professor who claims to be studying chimpanzees, and they head off into the jungle--but when the Professor disappears, Luc has to fend for himself and join forces with the chimps to save their forest.